2013
DOI: 10.1007/s10930-013-9465-6
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Composition and Extinction Coefficient of Native Botulinum Neurotoxin Complex Produced by Clostridium botulinum Hall A Strain

Abstract: Seven distinct strains of Clostridium botulinum (type A to G) each produce a stable complex of botulinum neurotoxin (BoNT) along with neurotoxin-associated proteins (NAPs). Type A botulinum neurotoxin (BoNT/A) is produced with a group of NAPs and is commercially available for the treatment of numerous neuromuscular disorders and cosmetic purposes. Previous studies have indicated that BoNT/A complex composition is specific to the strain, the method of growth and the method of purification; consequently, any var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…Although their reducing SDS-PAGE results show 7 bands for NAPs, it is still unclear what the molecular composition is. NAPs purified in our lab is passed through a G-100 Sephadex column before eluting it through an anion exchange column to remove the additional impurities and also its exact molecular composition has been determined [20]. Also, there is variation in the buffer and salt composition used for CD analysis in our experiments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although their reducing SDS-PAGE results show 7 bands for NAPs, it is still unclear what the molecular composition is. NAPs purified in our lab is passed through a G-100 Sephadex column before eluting it through an anion exchange column to remove the additional impurities and also its exact molecular composition has been determined [20]. Also, there is variation in the buffer and salt composition used for CD analysis in our experiments.…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated that the mechanism of toxin protection by HA-33 could be either due to the structural changes in the toxin by direct association with HA-33 or by potential blocking of the proteolytic cleavage sites on the toxin by HA-33, which renders the toxin protease-resistant in the GI tract. Based on these results and on further research, the exact molecular composition and a schematic model for BoNT/A complex was proposed showing the direct interaction of toxin with HA-33 [20]. Thus, the current research findings on the relevant roles of NTNH and Hn-33 in toxin protection strongly suggest that the stability of the toxin at acidic pH conditions of the stomach could be attributed to the protective action by NTNH, while HA-33 could be majorly involved in conferring proteolytic resistance to toxin in the protease-rich environment of the GI tract.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been performed to elucidate the biological and structural roles of the nontoxic botulinum complex proteins. Most of the studies have been performed on toxin complexes purified by chromatography or by in vitro reconstitution with recombinant BoNTs and nontoxic complex protein components expressed in Escherichia coli (45,(47)(48)(49). Structural studies of TCs have mainly used electron microscopy (EM), since high-quality crystals for X-ray diffraction of the LL and other complexes have not been obtained from native cultures.…”
mentioning
confidence: 99%
“…Clostridium species, however, naturally produce toxin complexes consisting of the core holotoxin in association with NAPs [62][63][64] . The NAPs protect the toxin from protease attack in the gastro-intestinal tract and are believed to facilitate toxin transport across the intestine epithelium 63,65 .…”
Section: Discussionmentioning
confidence: 99%